Biologic Modulators in Allergic and Autoinflammatory Diseases - Broderick, Lori (2011)
PURPOSE OF REVIEW: The advent of molecular techniques has resulted in the ability to tailor medications to specific protein targets. This review will emphasize several biological therapies, specifically directed toward cytokine receptors and inhibitors, and their role in the treatment of atopic and autoinflammatory diseases. RECENT FINDINGS: Translational research and the identification of the molecular pathophysiology of diseases have led to more targeted treatment approaches. The biologic modulators, encompassing monoclonal antibodies as cytokine inhibitors, receptor blocking antibodies and new fusion receptors are now being applied to diseases beyond their original application. SUMMARY: The expanded use of biological therapies has experienced success in the treatment of numerous disorders, especially in subsets of patients with disease that has been refractory to conventional therapies.